The Exploitation of Liposomes in the Inhibition of Autophagy to Defeat Drug Resistance - Condello, Maria; Mancini, Giovanna; Meschini, Stefania (Frontiers in Pharmacology, 2020)
Autophagy is a mechanism involved in many human diseases and in cancers can have a cytotoxic/cytostatic or protective action, being in the latter case involved in multidrug resistance. Understanding which of these roles autophagy has in cancer is thus fundamental for therapeutical decisions because it permits to optimize the therapeutical approach by activating or inhibiting autophagy according to the progression of the disease. However, a serious drawback of cancer treatment is often the scarce availability of drugs and autophagy modulators at the sites of interest. In the recent years, several nanocarriers have been developed and investigated to improve the solubility, bioavailability, controlled release of therapeutics and increase their cytotoxic effect on cancer cell. Here we have reviewed only liposomes as carriers of chemotherapeutics and autophagy inhibitors because they are the sole nanoparticles that are actually used as drug carriers in oncological clinical settings. In this review after the analysis of the dual role of autophagy, of the main autophagic pathways, and of the role of autophagy in multidrug resistance, we will focus on the most effective liposomal formulations, thus highlighting the great potential of these targeting systems to defeat cancer diseases.